Three-year trends in out-of-hospital cardiac arrest across the world: Second report from the International Liaison Committee on Resuscitation (ILCOR). (May 2023) - Nishiyama, Chika; Kiguchi, Tekeyuki; Okubo, Masashi; Alihodžić, Hajriz; Al-Araji, Rabab; Baldi, Enrico; Beganton, Frankie; Booth, Scott; Bray, Janet; Christensen, Erika; Cresta, Ruggero; Finn, Judith; et al.
Abstract: Background: The International Liaison Committee on Resuscitation (ILCOR) Research and Registries Working Group previously reported data on systems of care and outcomes of out-of-hospital cardiac arrest (OHCA) in 2015 from 16 national and regional registries. To describe the temporal trends with updated data on OHCA, we report the characteristics of OHCA from 2015 through 2017. Methods: We invited national and regional population-based OHCA registries for voluntary participation and included emergency medical services (EMS)-treated OHCA. We collected descriptive summary data of core elements of the latest Utstein style recommendation during 2016 and 2017 at each registry. For registries that participated in the previous 2015 report, we also extracted the 2015 data. Results: Eleven national registries in North America, Europe, Asia, and Oceania, and 4 regional registries in Europe were included in this report. Across registries, the estimated annual incidence of EMS-treated OHCA was 30.0–97.1 individuals per 100, 000 population in 2015, 36.4–97.3 in 2016, and 40.8–100.2 in 2017. The provision of bystander cardiopulmonary resuscitation (CPR) varied from 37.2% to 79.0% in 2015, from 2.9% to 78.4% in 2016, and from 4.1% to 80.3% in 2017. Survival to hospital discharge or 30-day survival for EMS-treated OHCA ranged from 5.2% to 15.7% in 2015, from 6.2% to 15.8% in 2016, and from 4.6% to 16.4% in 2017. Conclusion: We observed an upward temporal trend in provision of bystander CPR in most registries. Although some registries showed favourable temporal trends in survival, less than half of registries in our study demonstrated such a trend.